Prevalence of Hypertension and Diabetes in Children - Maktouf, Hassan Razzaq; Helal, Zainab Adnan; Kadhim, Shahad Khalid; Javat, Sattar Jabbar; Ahmed, Duha Kareem (Journal of Medical Genetics and Clinical Biology, 2024)
In 2017, the American Academy of Pediatrics issued a new clinical practice guideline for defining hypertension in children as an update to the previous Fourth Report guidelines issued in 2004. Prevalence of confirmed pediatric hypertension in children has ranged from 2% to 4% based on previous guidelines yet it is unknown what the prevalence is under the new guideline. We estimated the prevalence of elevated blood pressure, stage 1, and stage 2 hypertension by the new American Academy of Pediatrics guideline in our school-based blood pressure screening program. New prevalence estimates were compared with Fourth Report prevalence estimates in the same population by sex, age, and height factors. In 22 224 students aged 10 to 17 years screened in school as part of the Houston Pediatric and Hypertension Program at the University of Texas McGovern Medical School, the prevalence of elevated blood pressure (previously called prehypertension) increased from 14.8% by Fourth Report to 16.3% by the new American Academy of Pediatrics guideline. This increase in elevated blood pressure resulted from differential classification changes in younger and older children. Prevalence of confirmed hypertension remains at 2% to 4% in this population, however shorter children <13 years old and taller, older children 13+ years old are systematically more likely to be diagnosed with hypertension by new guidelines..